2015
DOI: 10.5248/129.373
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoglomus, a new genus of the Glomeraceae

Abstract: Rhizoglomus gen. nov. (Glomeraceae, Glomeromycetes) is proposed, typified by Glomus intraradices [≡ Rhizoglomus intraradices]. The genus encompasses species of arbuscular mycorrhizal fungi that frequently form abundant spores in soil and roots and is morphologically characterized by spores with cylindrical subtending hyphae (usually with an open pore at the base) and at least two or three (rarely up to five) distinct wall layers. Phylogenetically, the genus forms a separate clade in the Glomeraceae. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 22 publications
0
65
0
6
Order By: Relevance
“…To determine how nucleotide diversity (), rarefied OTU richness, and OTU diversity may vary across different taxonomic groups, we tested the magnitude and statistical significance of variance components corresponding to AM fungal genera, species, and isolates using mixed models with the MIXED procedure in SAS (v.9.4; SAS Institute, Inc., Cary, NC). We followed the consensus AM fungal genus names proposed previously (52), except for Rhizoglomus instead of Rhizophagus (20) and Claroideoglomus and Entrophospora, which we considered the same genus for statistical tests (see Results and Discussion). Total variance was calculated as the sum of the variances explained by differences among isolates, species, and genera and was considered to be significantly different from zero if at least one of those variance components was significantly different from zero.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine how nucleotide diversity (), rarefied OTU richness, and OTU diversity may vary across different taxonomic groups, we tested the magnitude and statistical significance of variance components corresponding to AM fungal genera, species, and isolates using mixed models with the MIXED procedure in SAS (v.9.4; SAS Institute, Inc., Cary, NC). We followed the consensus AM fungal genus names proposed previously (52), except for Rhizoglomus instead of Rhizophagus (20) and Claroideoglomus and Entrophospora, which we considered the same genus for statistical tests (see Results and Discussion). Total variance was calculated as the sum of the variances explained by differences among isolates, species, and genera and was considered to be significantly different from zero if at least one of those variance components was significantly different from zero.…”
Section: Methodsmentioning
confidence: 99%
“…However, in contrast to most other microbes, in AM fungi, this sequence variation can occur within a single multinucleate cell (18,19). While recent genome sequencing of isolates of the genus Rhizoglomus (20) has expanded our understanding of genetic variation in AM fungi beyond the rRNA genes (21)(22)(23), it remains largely unknown how either genome-wide or rRNA gene sequence variation may itself differ across evolutionary lineages. Previous studies that sampled a limited amount of rRNA gene sequence variation found that sequences from morphologically defined species generally formed clades on the gene tree (24)(25)(26), which is an essential prerequisite for clustering sequences into species-level OTUs.…”
mentioning
confidence: 99%
“…In this work we adopted the classification proposed by Oehl et al (2011), including recently described new taxa (i.e. Goto et al 2012 andSieverding et al 2014). After AMF species identification, provide directly from field, we calculated the following ecological index: diversity index (H) proposed by Shannon & Weaver (1949), and dominance index (C) proposed by Simpson (1949) for each studied AMF community.…”
Section: Site Description and Sampling Methodsmentioning
confidence: 99%
“…Species identification was based on the descriptions provided by Schenck and Perez (1987), publications with descriptions of new families and genera (i.e., Oehl et al 2008), and by consulting the international culture collection of arbuscular mycorrhizal fungi database-INVAM (http://invam.caf.wvu.edu). In this work, we followed the classification proposed by Oehl et al (2011), including recently new described taxa (i.e., Goto et al 2012;Redecker et al 2013;Sieverding et al 2014). In addition to species identification, we also assessed spore abundance by counting the total number of spores, spore abundance of each AMF species by recording the number of spores of each AMF species recorded in the samples, and the species occurrence frequency (FOi) of each AMF species.…”
Section: Arbuscular Mycorrhizal Fungi Community Characterizationmentioning
confidence: 99%